The The Legitimized Use of Figurative Language: A Pragmatic Study of Multiculturalism and Political Intrigues of Shamsie's "Burnt Shadows" - Nida ul Zafar; Aamna Safdar; Safdar Abbas (Nicolaus Copernicus University in Toruń, 2022)
The study explores the legitimized use of the figure of speech in Burnt Shadows. The author uses language as a source of connection between the characters who are different in their eras, countries, and cultural backgrounds. The objective of the study is to explore the effects of language on multiculturalism and the impact of political unrest on the lives of common people during the second world war. She has used lingual devices to enhance the intensity of circumstances as well as for the accurate pasteurization of the sentimental and physical conditions of Hiroko and Sajjad. Specific figurative techniques like metaphor, simile, personification, irony, epigram, and symbolism have been explored in the text of Burnt Shadows. These techniques expose the hidden truths and aggressive nature of political conflict in the lives of the people of Japan, the Subcontinent, and European countries. Pragmatic studies have been applied to the text as a mirror to see the function and nature of wordplay in the novel. The results expose that the author has artistically applied specific devices in the formation of text in order to highlight the role of language in the development of cultural intimacy and maintaining social relationships. The figures of speech are also helpful to map the mind of readers according to the plot construction of the novel.